The impact of the minimum subsistence on wage in Kazakhstan - Кыстаубаева, A. (Journal of Economic Research & Business Administration, 2017)
In this paper it is considered the dependence of wages (y) from the average per capita subsistence level (x) for the able-bodied population of Kazakhstan. To do this, it is conducted a survey of fourteen regions of Kazakhstan for 2016. Data per capita subsistence minimum in September 2016 for the able-bodied population of Kazakhstan and the average monthly salary for the third quarter 2016 are used. Then, the data is processed to construct the model. Assuming that there is a linear relationship between variables, sample regression equation is defined. The model is built according to per capita subsistence minimum and average wages in the regions of Kazakhstan for 2016. The coefficients of the regression equation are defined by the least squares method. It is explained meaning of the regression coefficients. We calculate the correlation coefficient for the selected sample on which to draw conclusions. The paper is included the graphics of raw data (scatter plot) and schedule data combined with the regression equation.